Effect of Service Quality on Decision to Choose a School with Fanaticism and Character Building as Moderating Variable (Case Study at Yadika Bangil Vocational High School) - Fahmi Abdullah (Budapest International Research and Critics University, 2022)
This study aims to analyze effect of service quality on decision to choose a school with fanaticism and character building as moderating variable in case study at Yadika Bangil Vocational High School. The population are 61 parents of class X students of Yadika Bangil Vocational High School. The sampling method use probability sampling and a sample of 53 respondents is obtain from the parents of class X students of Yadika Bangil Vocational High School. Methods of data analysis using regression analysis. The results of this study indicate that service quality has a positive and significant effect on decision to choose a school at Yadika Bangil Vocational High School. Fanaticism cannot moderate effect of service quality on decision to choose a school at Yadika Bangil Vocational High School. Character building cannot moderate effect of service quality on decision to choose a school at Yadika Bangil Vocational High School.